Impacts of university lockdown during the coronavirus pandemic on college students’ academic achievement and critical thinking: A longitudinal study - Lv, Xiaojing; Ma, Juanjuan; Brinthaupt, Thomas M.; Zhao, Shaochun; Ren, Xuezhu (Frontiers in Psychology, 2022)
This paper examined college students’ changes of learning outcomes and clarified what might explain individual differences in students’ learning outcomes after they had learned from home for a whole semester when universities were physically closed due to the COVID-2019 pandemic. Data were derived from a longitudinal study examining students’ academic achievement and critical thinking (including both skills and dispositions) before and after the university lockdown. We observed significant decreases in critical thinking skills and dispositions from pre- to post-lockdown. Both perceived academic achievement and critical thinking exhibited greater variability after the lockdown. In addition, students’ readiness for online learning, especially their self-management skills, consistently predicted post-lockdown learning outcomes after pre-lockdown outcomes and family SES were controlled for. Those who have assumed more responsibilities at home, or who were more vulnerable to emotional distress during the pandemic, performed less well in post-lockdown learning outcomes.